Response of IAPAR-59 coffee (Coffea arabica L.) to surface applied organic residues in a typic haplorthox - Fidalski, Jonez; Chaves, Júlio César Dias (Coffee Science - ISSN 1984-3909, 2010)
The objective of this work was to assess the soil fertility, nutritional status, vegetative growth and yield of coffee cv. Iapar-59, subjected to four exogenous applications (2002-2004): 20 t ha-1 dry matter (grey mucuna, leucaena, pigeon pea, perennial peanut, brizantha grass, forage sorghum, sugarcane bagasse, filter cake-sugarcane, citrus bagasse, sewage sludge, sewage sludge and lime, coffee straw, manure (bovine), chicken litter, chicken manure, sugarcane bagasse and chicken manure, swine manure; 200 m3 ha-1 liquid swine manure; N (95 kg ha-1 ammonium sulphate). A field experiment was set up in 2002, in a Typic Haplorthox, in Paranavaí, northwestern region of Paraná state, Brazil. From 2003 to 2005 soil (0-5, 5-10, 10-20 e 20-40 cm) and leaf samples were collected and coffee tree growth and yield were assessed. Grey mucuna increased leaf N, leucaena increased soil K (5-40 cm) and filter cake-sugarcane increased soil Ca (10-40 cm). These alterations were closely related to higher coffee growth rates and yield.